Cardiac compromise in AIDS. First peruvian report - VALENZUELA, GERMÁN (2004)
Objective: To determine the patterns of cardiac compromise in patients infected by human immunodeficiency virus in AIDS-stage. Material and Methods: Prospective study of ambulatory patients at Guillermo Almenara Irigoyen National Hospital between March 2002 and March 200, included assessment of clinical and epidemiological parameters and echocardiographic study. Results: One hundred and thirty-two patients were studied. They had a mean age of 40,4 years (SD 8,7). The median time for AIDS diagnosis was 48 months (IQR 50) and received antiretroviral therapy 63,6%. Cardiac compromise patterns were diastolic dysfunction (DD) in 28,8%, systolic dysfunction in 3,0%, pericardial effusion in 9,1%. DD was associated with a history of previous hospitalization and older age. Conclusions: We found a high percentage of cardiac abnormalities in patients with HIV infection in AIDS stage. DD was the most frequent finding.